The Influence Of The Tahfidzul Qur’an Program On The Character Forming Of The Nurul Huda Islamic Boarding School - Ahmad Nawawi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The decline in character has become a common sight that is clearly seen in the daily livesof teenagers. Therefore, it is necessary to carry out various efforts from educationalinstitutions to return humans to goodness, as well as prevent the growth and developmentof negative characters in students, as early as possible. One program that is able to shapethe character of students is the Tahfidzul Qur'an program. With the program to memorizethe Qur'an, students will know better what to do and what to leave behind. This studyaims to prove the influence of the Tahfidzul Qu'ran program on the character formation ofthe students of the Nurul Huda Islamic Boarding School Purbalingga. Samples were takenas many as 100 students of the Islamic Boarding School Nurul Huda Purbalingga. Thedata analysis technique used is simple linear regression.The results showed that the tahfidzul qu'ran program had an effect on the formation of thecharacter of students. Tahfidz Al-Qur'an education at the Islamic Boarding School NurulHuda Purbalingga serves as an introduction, habituation, and inculcation of noblecharacter values to students in order to build people of faith and piety to Allah SWT. Aperson's character is formed through habits that are carried out. If good habits are carriedout by someone, a good character will be formed, as well as if what is accustomed is badthings, it will form a character that is not in a person. The formation of the character ofstudents is very important and should not be ignored by anyone for the future of the nationand the maintenance of religion. The formation of the character of students is theresponsibility of every person, family, school, community, and government.